2012
DOI: 10.3998/ark.5550190.0013.313
|View full text |Cite
|
Sign up to set email alerts
|

A short and efficient synthesis of (+)-totarol

Abstract: A concise route to multigram quantities of the antibacterial diterpene (+)-totarol (1) is reported. (−)-Sclareol (2) was converted to the target compound 1 using either a six-or a seven-step sequence, while only three steps were required to access (+)-totarol (1) starting from (+)-manool (9) or (+)-13-epi-manool (10), respectively. A novel one-pot intramolecular aldol condensation/ α-alkylation protocol served as the key operation for streamlining the syntheses of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A further derivative of sclareol was obtained by acetylation of both alcoholic functions by acetyl chloride in the presence of N , N -dimethylaniline in dichloromethane, giving compound 3 , and subsequent selective hydrolysis by KOH in ethanol leading to compound 4 . The latter was subjected to an E1 elimination by using NaHCO 3 in DMSO, as described by Rogachev et al, with some modifications using microwave conditions (200 °C, 100 W, 11 min); this procedure led to the synthesis of compound 5 as a geometric isomeric mixture (2:1 exo/endo isomer mixture, as determined by 1 H NMR integration; see Supporting Information, S2). The obtained dehydrated derivative was subjected to the Heck-reaction, with yields and reaction times improved by microwave conditions (130 °C, 300 W, 12 min), leading to compound 6 .…”
Section: Resultsmentioning
confidence: 99%
“…A further derivative of sclareol was obtained by acetylation of both alcoholic functions by acetyl chloride in the presence of N , N -dimethylaniline in dichloromethane, giving compound 3 , and subsequent selective hydrolysis by KOH in ethanol leading to compound 4 . The latter was subjected to an E1 elimination by using NaHCO 3 in DMSO, as described by Rogachev et al, with some modifications using microwave conditions (200 °C, 100 W, 11 min); this procedure led to the synthesis of compound 5 as a geometric isomeric mixture (2:1 exo/endo isomer mixture, as determined by 1 H NMR integration; see Supporting Information, S2). The obtained dehydrated derivative was subjected to the Heck-reaction, with yields and reaction times improved by microwave conditions (130 °C, 300 W, 12 min), leading to compound 6 .…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] The chemistry therefore appears to support this taxonomic realignment. Compounds 1, 2, 5, 6, 8-14 have been previously isolated as natural products with some also being the focus of synthetic studies, [12][13][14][15] providing sufficient characterisation data for comparison. The synthesis of 3 has been reported 10 but there has been no previous reports of its occurrence as a natural product.…”
Section: Root Barkmentioning
confidence: 99%
“…The preliminary GCMS screening of an n-hexane extract of D. obscura leaves did not indicate the presence of denhaminols but four pentacyclic triterpenes were identified as significant components of the extract: lupen-3-one (15); germanicone (16); -amyrone (17); and friedelin (friedelan-3-one) (12) (Figure 2). Extraction of the leaves with more polar dichloromethane resulted in the isolation of 12, 15-17 as well as glutinol (14) and lupeol (18), while extraction with methanol produced an extract rich in α-glucose, -glucose and -xylose.…”
Section: Leavesmentioning
confidence: 99%
“…The three steps conversion of 5 to (+)-nimbidiol 3 has been reported previously. 10,11 In 2012 Rogachev et al 26 reported the synthesis of (+)-totarol 19 using the diketone 21, obtained in one step from (+)-manool 1 in 48% yield by ozonolysis in the presence of sodium hydroxide at -10 °C (Scheme 7). Compound 21 was converted to the intermediate 24 in a one-pot reaction with t-BuOK, tert-butanol (t-BuOH) and isopropyl iodide (i-PrI) at refluxing temperature in 56% yield.…”
Section: Ring C Aromatic Diterpenesmentioning
confidence: 99%